Internal Displacement to Urban Areas: the Tufts-IDMC Profiling Study (Khartoum, Sudan) - Jacobsen, Karen (Tufts Archival Research Center, 2005)
In recent decades Sudan's North-South civil war and the Conflict, Armed (War) in Darfur have generated one of the largest internally displaced populations in the world. A large proportion of these IDPs is found in and around the capital, Khartoum. The Tufts-IDMC study of Khartoum was a pilot for our larger study and was carried out in 2007, two years after the signing of the Comprehensive Peace Agreement. While the CPA raised hopes for the return of IDPs, continuing insecurity, lack of services in areas of return and doubts about the sustainability of the CPA, have slowed the pace of return.